The Relationship Level of Husband's Knowledge About Postpartum Care to Caring In Mothers In The Work Area of Handapherang Puskesmas - Srinayanti, Yanti; Litasari, Resna; Andrian, Aang; Ariani, Dini (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The term "childbirth" or "postpartum" refers to the period needed by a mother to recover and return her uterus to its original state after giving birth to a baby. This process begins after the first 2 hours of labor and continues for 6 weeks (42 days). During this recovery phase, the mother will experience various changes both physically and physiologically. This period has an important role for the medical team and the family, especially the husband, because inadequate monitoring can increase the risk of maternal death. Caring or a caring attitude from the husband is very crucial during this postpartum phase. Caring attitude includes care, appreciation, and respect for mothers. This involves paying attention to the mother's preferences and actions, as well as understanding her thoughts and behavior. Caring is not just based on trivial emotions or actions, but is a deeper form of caring to ensure optimal care. Caring attitudes aim to build social structures, reinforce beliefs about life, and encourage values in the relationship between husband and wife, or in the family as a whole. Purpose: to determine the relationship between the husband's level of knowledge and caring for mothers in the working area of the handapherang health center. The research used is a quantitative research. Method: the instrument for data collection used a questionnaire while the sample was taken using total sampling technique with 33 respondents who were postpartum. Results: the results of the analysis using the chi square test the level of knowledge of husbands about postpartum care with a percentage of 57.6%, caring for mothers with a percentage of 51.1%. Conclusion: from the results of the study it can be concluded that there is a relationship between the husband's level of knowledge about postpartum care and caring for the mother with p=value 0.028 â‰¤ 0.05.